1995
DOI: 10.1111/j.1528-1157.1995.tb01671.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of L‐Type Calcium Channel Modulation in Nonconvulsive Epilepsy in Rats

Abstract: Summary: Old male Wistar rats spontaneously showing hundreds of spike-wave discharges daily were used to investigate the role of calcium ions in nonconvulsive epilepsy. The effects of the L-type calcium channel blocker nimodipine and the L-type channel opener BAY K 8644 on number and duration of these spike-wave discharges were investigated. In rats aged 84-94 weeks standard EEG electrodes were chronically implanted; animals were allowed to recover for 10 days. After a baseline registration, nimodipine 2.2, 8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 38 publications
4
31
1
Order By: Relevance
“…As previously reported, old Wistar rats show spike-wave discharges [34,35], and the morphology of the spike-wave discharges does not appear to be different from the ones we frequently study in WAG/Rij rats, a genetic model of human absence epilepsy [5,6,32]. The spike-wave suppressant effects of CGP 35348 are strong and long-lasting, and the effects are dose-dependent in the whole dose range and in all 3 h. The efficacy of GABAB antagonists against spike-wave discharges is unchallenged, as is evident from recent studies in various models for generalised absence epilepsy [ 11,16,17,18,28 ].…”
Section: Discussionsupporting
confidence: 56%
“…As previously reported, old Wistar rats show spike-wave discharges [34,35], and the morphology of the spike-wave discharges does not appear to be different from the ones we frequently study in WAG/Rij rats, a genetic model of human absence epilepsy [5,6,32]. The spike-wave suppressant effects of CGP 35348 are strong and long-lasting, and the effects are dose-dependent in the whole dose range and in all 3 h. The efficacy of GABAB antagonists against spike-wave discharges is unchallenged, as is evident from recent studies in various models for generalised absence epilepsy [ 11,16,17,18,28 ].…”
Section: Discussionsupporting
confidence: 56%
“…To date, there are not enough literature data obtained from the use of PUFAs in absence epilepsy that we can use to compare with these results. In studies on the modulation of Ca 2+ channels in absence epilepsy, it was found that the T-type channel blockage decreased the SWDs, while the L-type channel blockage increased the SWDs (9). The findings that the Ca 2+ channels inhibited by PUFAs are particularly L-type channels show that the inhibition of L-type Ca 2+ channels may be an important factor in the development of the SWD-increasing effect of linoleic acid.…”
Section: In Terms Of Nonconvulsive Epilepsy (Absence)mentioning
confidence: 90%
“…In the classical EEG pattern there are spikewave discharges (SWDs) accompanying the seizure (2,8). There are many studies showing that GABAA and GABAB receptors are involved in the generation of SWDs (9,10). An increase in GABAergic activity can induce the generation of SWDs by increasing the intensity of the absence seizures in humans and animal models through inhibition and synchronization of neuronal firing.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, the seizure occurs due to the entry of calcium ions into nerve cells and reducing intracellular calcium concentration in some epileptic animal models has inhibitory effect on seizures. During seizures increased intracellular calcium ion concentration and but extra cellular calcium concentration decreases (Khanna et al, 2000;Van Luijtelaar et al, 1995). Calcium channel antagonists for the treatment of hypertension were produced in the year 1980.…”
Section: Introductionmentioning
confidence: 99%
“…Specific drugs used to treat epilepsy are absence seizure kind of like channels as T-type calcium in thalamic neurons are blocked. This reduced calcium ion concentration of the important goals in development is neuroprotective and antiepileptic drugs (Kulak et al, 2004;Van Luijtelaar et al, 1995). Calcium entry into neurons play an important role in creating the seizures and calcium channel inhibitors have different effects on health, including cardiovascular diseases, migraine and headaches caused by vascular changes, nerve regeneration and neuronal regenerative processes (Khanna et al, 2000), So it seems calcium channel inhibitors used to treat seizures can be useful.…”
Section: Introductionmentioning
confidence: 99%